Micro-vibration assisted dual-layer spiral microneedles to rapidly extract dermal interstitial fluid for minimally invasive detection of glucose - Khaled Mohammed Saifullah; Asim Mushtaq; Pouria Azarikhah; Philip D. Prewett; Graham J. Davies; Zahra Faraji Rad (Microsystems & Nanoengineering)
Abstract Various hydrogels have been explored to create minimally invasive microneedles (MNs) to extract interstitial fluid (ISF). However, current methods are time-consuming and typically require 10–15 min to extract 3–5 mg of ISF. This study introduces two spiral-shaped swellable MN arrays: one made of gelatin methacryloyl (GelMA) and polyvinyl alcohol (PVA), and the other incorporating a combination of PVA, polyvinylpyrrolidone (PVP), and hyaluronic acid (HA) for fast ISF extraction. These MN arrays demonstrated a rapid swelling ratio of 560 ± 79.6% and 370 ± 34.1% in artificial ISF within 10 min, respectively. Additionally, this study proposes a novel method that combines MNs with a custom-designed Arduino-based applicator vibrating at frequency ranges (50–100 Hz) to improve skin penetration efficiency, thereby enhancing the uptake of ISF in ex vivo. This dynamic combination enables GelMA/PVA MNs to rapidly uptake 6.41 ± 1.01 mg of ISF in just 5 min, while PVA/PVP/HA MNs extract 5.38 ± 0.77 mg of ISF within the same timeframe. To validate the capability of the MNs to recover glucose as the target biomarker, a mild heating procedure is used, followed by determining glucose concentration using a d-glucose content assay kit. The efficient extraction of ISF and glucose detection capabilities of the spiral MNs suggest their potential for rapid and minimally invasive biomarker sensing.